2014
DOI: 10.2133/dmpk.dmpk-13-rg-105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Human Hepatocytes Cultured by Three-dimensional Spheroid Systems for Drug Metabolism

Abstract: We investigated the utility of three-dimensional (3D) spheroid cultures of human hepatocytes in discovering drug metabolites. Metabolites of acetaminophen, diclofenac, lamotrigine, midazolam, propranolol and salbutamol were analyzed by liquid chromatography-tandem mass spectrometry (LC/MS/MS) to measure enzyme activities in this system cultured for 2 and 7 days. Sequential metabolic reactions by Phase I and then Phase II enzymes were found in diclofenac [CYP2C9 and UDP-glucuronyltransferases (UGTs)], midazolam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 31 publications
0
50
1
1
Order By: Relevance
“…Future work may include testing our cell and assay system with more DILI-positive and -negative compounds, although the number of compounds tested is on par with other research in this area, where an average of eight compounds are tested per experiment. 18,19,24,26,[32][33][34][35][36][37][38] Interlaboratory comparison between the few hepatotoxicity studies conducted on 3D HepaRGs and 3D primary hepatocytes revealed similarities and differences in the reported IC 50 values ( Table 3). While the reported IC 50 values for tetracycline were similar in the 3D HepaRG studies, the amiodarone and rosiglitazone results varied, with our 3D HepaRG cells responding more sensitively to the liver toxins by one to two orders of magnitude than those of Mueller et al 36 and Gunness et al 33 The differing IC 50 values for rosiglitazone and amiodarone may be due to the spheroid generation method (e.g., hanging drop method, U-bottom, additive manufacturing, and biomaterial scaffolding), spheroid maturity, cell culture conditions, and viability endpoint measurement (e.g., ATP depletion and albumin production).…”
Section: Discussionmentioning
confidence: 99%
“…Future work may include testing our cell and assay system with more DILI-positive and -negative compounds, although the number of compounds tested is on par with other research in this area, where an average of eight compounds are tested per experiment. 18,19,24,26,[32][33][34][35][36][37][38] Interlaboratory comparison between the few hepatotoxicity studies conducted on 3D HepaRGs and 3D primary hepatocytes revealed similarities and differences in the reported IC 50 values ( Table 3). While the reported IC 50 values for tetracycline were similar in the 3D HepaRG studies, the amiodarone and rosiglitazone results varied, with our 3D HepaRG cells responding more sensitively to the liver toxins by one to two orders of magnitude than those of Mueller et al 36 and Gunness et al 33 The differing IC 50 values for rosiglitazone and amiodarone may be due to the spheroid generation method (e.g., hanging drop method, U-bottom, additive manufacturing, and biomaterial scaffolding), spheroid maturity, cell culture conditions, and viability endpoint measurement (e.g., ATP depletion and albumin production).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, metabolic activity towards several drugs in our spheroid system was found to be stable from day 7 to day 21 in our previous study. Therefore, the spheroid assay system is considered to be suitable for detection of toxicity associated with sequential metabolic reactions and human-specific metabolites that are difficult to identify by means of conventional assays (Ohkura et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that human hepatocyte spheroids are suitable for long-term metabolic assays (Ohkura et al, 2014), and we identified sequential metabolic reactions of diclofenac, midazolam and propranolol by Phase I and Phase II enzymes. Moreover, lamotrigine and salbutamol were metabolized to lamotrigine-N-glucuronide and salbutamol 4-O-sulfate, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond two-dimensional cultures of primary or immortalized hepatocytes, three-dimensional and co-cultures are becoming readily available (Godoy et al, 2013). Examples include HepatoPac (Chan et al, 2013), hepatocyte spheroids (Ohkura et al, 2014), and HmREL (Novik et al, 2010), all of which have been shown to maintain liverspecific functions for several days. A recent article has reviewed the available literature on different CL int assays, with particular emphasis on slowly metabolized compounds and advantages or disadvantages with regard to prediction of human hepatic CL .…”
Section: Introductionmentioning
confidence: 99%